Nanofios de Ge : síntese e dispositivos - Kamimura, Hanay (Universidade Federal de São Carlos, 2012)
Abstract In this work, germanium nanowires' based devices were studied and developed and the influence of natural disorder on the electronic properties of these structures was also investigated. Parameters related to the current transport mechanisms, such as electron mobility, localization length and Schottky barrier height were determined. Such investigations were carried out initially by the fabrication of germanium nanowires using the vapour-liquid-solid method with gold nanoparticles acting as catalysts for the growth process. Morphological and structural characterizations were performed to obtain information about the material: the X-ray di_raction analysis showed a good agreement with the cubic structure of germanium and its diamond-like structure; by scanning and transmission electron microscopy it was found samples with diameter from 20 to 150 nm and length up to tens of micrometers. Furthermore, these techniques allowed the observation of an oxide layer on the surface of the nanowires, whose disordered interface originates localized states, which can also be responsible for changes in electronic properties of the system. Di_erent types of devices were developed for the investigation of the electronic transport in germanium nanowires. The experiment performed on each device allowed the analysis of the disorder's influence on the measured properties: electronic transport within the temperature ranges used for the experiments was dominated by the variable range hopping mechanism, characteristic of disordered systems instead of the expected thermal excitation, typical of semiconductor materials. Further confirmation of these data was obtained using transistor devices and the carrier mobility was found to be lower than the commonly observed values for germanium. These data also agree with the fact of disordered systems exhibits low mobility values due to the presence of localized states. Finally, it was used a device specially designed for the study of the metal/nanowires interface characteristics. In order to determine the Schottky barrier height a two barriers model was used (including temperature dependence). The obtained values (from 0.48 to 0.54 eV ) were di_erent from the usual (0.58 eV for germanium/aluminium contact), which also shows and con_rms the presence of localized states at the metal/nanowire interface, following Bardeen's model for the Schottky barrier formation. To complement this analysis theoretical simulation values for Schottky barrier (∼ 0.5 eV ) were calculated taking into account the contribution of surface states. This value corresponding to density of states of 1012 ∼ 1013cm−2eV −1. Comparing both theoretical and experimental Schottky barrier heights, the presence of localized states generated by disorder was confirmed.
Keywords: Semicondutores; Germânio; Transporte eletrônico; CIENCIAS EXATAS E DA TERRA::FISICA